Tingkat Keterampilan Smash Pada Atlet Bulutangkis - Hasanuddin, M. Imran; Syafruddin, muhammad Akbar; Sutriawan, Agus (STAMINA, 2023)
The purpose of this study was to determine the level of smash skills in BKMF FIK UNM badminton athletes. This type of research is descriptive quantitative with survey methods while the technique and data collection uses tests and measurements. The population of this study were all BKMF FIK UNM badminton athletes and the sample in this study were 20 BKMF FIK UNM badminton athletes using a purposive sampling technique. The results showed that the smash skill level of BKMF FIK UNM badminton athletes obtained the "Very Good" category of 25% (5 athletes), the "Good" category of 50% (10 athletes), the "Enough" category of 20% (4 athletes) , the “Less” category is 5% (1 athlete), and the “Very Less” category is 0% (0 athletes). It can be concluded that the smash skill level of BKMF FIK UNM badminton athletes is in the good category.